Komparasi Efisiensi Bank Umum Konvensional Pemerintah dan Bank Umum Konvensional Swasta dengan Pendekatan Data Envelopment Analysis - Susila, Muktar Redy; Nugroho, Wawan Cahyo; Arini, Dian (Fakultas Ekonomi Universitas Samudra, 2024)
The research aim is to compare the level of efficiency between government-owned conventional commercial banks and privately owned conventional commercial banks. The samples are government-owned and privately owned conventional commercial banks registered in the period 2018 to 2022. The input variables used are deposits, labor costs and fixed assets; while output variables include total credit and operating income. Efficiency scores were analyzed using the data envelopment analysis method, and for the difference test the Mann-Whitney method was used. The results show that there is no significant difference in efficiency scores between government-owned conventional commercial banks and privately owned conventional commercial banks.